2016
DOI: 10.15406/htij.2016.02.00051
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Emergencies and Transfusion Needs in a Nigerian Hospital

Abstract: IBlood transfusion plays a significant role as a life-saving practice in emergency obstetrics and it is one of the essential components of comprehensive emergency obstetric care yielding a reduction in maternal mortality. While transfusion is commonly used to combat anaemia in obstetric practice, the majority of patients receiving transfusion are given to otherwise healthy women in response to undiagnosed obstetric hemorrhage. This study explores the need and blood transfusion rate among obstetrics patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…PPH is usually troublesome as it can cause massive haemorrhage. Similar to present study, PPH was the second common cause of BT (32.6%) in the study by Akingbola et al 14 In study by Bangal et al accidental haemorrhage was the second most common cause (20.92%). 13 Even in a similar study by Renuka et al postpartum haemorrhage was the second common cause for blood transfusion present in 21.54% patients.…”
Section: Obstetric Disorders Requiring Blood Transfusionsupporting
confidence: 89%
See 3 more Smart Citations
“…PPH is usually troublesome as it can cause massive haemorrhage. Similar to present study, PPH was the second common cause of BT (32.6%) in the study by Akingbola et al 14 In study by Bangal et al accidental haemorrhage was the second most common cause (20.92%). 13 Even in a similar study by Renuka et al postpartum haemorrhage was the second common cause for blood transfusion present in 21.54% patients.…”
Section: Obstetric Disorders Requiring Blood Transfusionsupporting
confidence: 89%
“…13 Akingbola et al reported that the overall transfusion rate was 2.2%; 78.7% were transfused at delivery and 22.3% were transfused during pregnancy. 14 The rate of requirement of blood in the studies may vary due to the complexity of cases observed at the facility, due to its status as a tertiary institution as well as referral centre and booking status. This difference in findings of studies could also be explained by different transfusion practices among institutions, low availability of donor blood in our environment, or case mix.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most patients in the lower-middle-income country category were from Nigeria and Pakistan. One study found that many obstetric patients at one of the trial sites-University College Hospital, Ibadan-received single unit blood transfusions despite the need for additional units, based on estimated blood loss or low hematocrit values [48,49]. Similarly, in Pakistan, a 40% shortage of blood and blood components limits the amount of donated blood available for transfusion [50].…”
Section: Plos Onementioning
confidence: 99%